Atividade inseticida e repelência de óleos essenciais em Tribolium castaneum herbst (Coleoptera: Tenebrionidae) - BRITO, Amaury Soares de (2015)
Tribolium castaneum is a secondary pest that causes quantitative and qualitative losses in grain stocks of various cereals and derivatives. Your control is performed with several applications of insecticides and the consequence of this practice is the environmental contamination of people and the selection of resistant insects populations. New methods of control, such as the use of essential oils are gaining strength to mitigate negative impacts. Following this line of reasoning the objective of this study was to evaluate the fumigant action, contact and repellent of essential oils in control of T. castaneum. Were used essential oils of plants Eucalyptus citriodora Hook (Myrtaceae), Foeniculum vulgare Mill (Lamiaceae), Cymbopogon winterianus Jowitt (Poaceae), Citrus sinensis (L) Osbeck (Rutaceae), Citrus aurantium, Croton helitropiifolius Kunth, Croton blanchetianus Baill and Croton pulegiodorus Baill (Euphorbiaceae). In fumigation different concentrations of test oils were applied on filter paper strips attached on the bottom of the fumigation chamber cover (0.5 L), which contained 20 grams of food substrate and 20 adults of T. castaneum unsexed. The insect mortality was recorded after 120 hours of exposure in B.O.D kiln incubator, at 30 °C and RH 70±5%. For the contact test, different concentrations of the oils were diluted in acetone and applied to filter paper disks (9 cm ∅) and the control was applied only acetone. After evaporation of the solvent, the disks were placed in petri dishes and 20 adult insects released unsexed, and the mortality was assessed after 24 hours of exposure in BOD. The repellency tests were performed in arenas composed of two pots connected to a central box. In a pot of one end moistened feed substrate was mixed deposited with concentrations of the essential oil diluted in acetone, in the other pot (control) was deposited only food; Twenty insects do not sexed adult were released in the central box, being exposed for 48 hours to evaluate the preference. Was used a completely randomized design with four replications; data fumigation tests were submitted to regression analysis, and the contact tests submitted to probit analysis. The repellent rate was calculated by the formula IR=2*(G+P) and the percentage of repellency (PR) by the formula [PR=(NC-NT)/(NC+NT)*100]. In fumigation tests C. aurantium oil showed 100% mortality at a concentration of 490 μL/L air, and F. vulgare 93% mortality at the concentration of 900 μL/L air. In contact tests for E. citriodora were obtained LC50 =0.5035 μL/cm2 and CL99 = 0.8478 μL/cm2. For C. winterianus were estimated LC50 = 0.9760 and 5.1983 CL99 = μL/cm2. F.vulgare got the lowest concentrations with LC50 = 0.0157 and CL99 = 0,0216 μL/cm2. The oils of E. citriodora and C. winterianus showed repellent effect and C. winterianus and F. vulgare reduced adult emergence.